Videolaparoscopic colectomy valid option? - Filártiga, Aníbal; Frétes, Ricardo; Wattiez, Carlos Raúl; Giménez, Alejandro; Román, Carlos; Martínez, Mirtha; Rovira, Alberto (Cirugía del Uruguay, 1999)
Videolaparoscopy (VL) is becoming the new approach method for the colorectal surgeon, because of its postoperatory advantages. The results of the first right colectomy assisted by VL in the Fírst Dívísion of Clínica! Surgery are presented and the revíews made are assessed.